Investigation of the treatment efficiency of fine-dispersed slime of a water rotation cycle of a metallurgical enterprise - Shkop, Andrii; Briankin, Oleksandr; Shestopalov, Oleksіi; Ponomareva, Natalya (Technology audit and production reserves, 2017)
The features of the water rotation cycle and the slime treatment system of the oxygen-converter shop of metallurgical production are investigated. During the audit, it is revealed that the concentration of suspended solids in the water cycle system varies in time up to 500 g/l for the condensed slime and up to 85 g/l in the pre-clarified water. It is established that the slimes of the metallurgical enterprise contain a finely dispersed solids fraction in the slime up to 93 % of a size of less than 20 μm and the residues of a cationic flocculant that impede effective treatment of the slime in the sedimentation tanks. This leads to the following drawbacks: a decrease in the slime treatment efficiency, removal of the fine fraction of solids together with clarified water of radial thickeners, regular replenishment of clean water, discharge of part of the flow into the slime collector. It is proposed to install an additional treatment module and use a more efficient anionic flocculant. It is recommended to monitor the efficiency of treatment and dosing of the flocculant depending on the solids concentration in the slime by continuous sampling and testing of slime flocculation. It is established that effective treatment up to 99 % can be achieved on the treatment module using anionic flocculant, thin-layer sedimentation tanks and sedimentation horizontal screw centrifuges.